HIV-1 Adaptation to Antigen Processing Results in Population-Level Immune Evasion and Affects Subtype Diversification - Tenzer, S; Crawford, H; Crawford, H; Pymm, P; Pymm, P; Gifford, R; Sreenu, V; Weimershaus, M; deOliveira, T; deOliveira, T; Burgevin, A; Gerstoft, J; et al. (2014)
The recent HIV-1 vaccine failures highlight the need to better understand virus-host interactions. One key question is why CD8+ Tcell responses to two HIV-Gag regions are uniquely associated with delayed disease progression only in patients expressing a few rare HLA class I variants when these regions encode epitopes presented by ~30 more common HLA variants. By combining epitope processing and computational analyses of the two HIV subtypes responsible for ~60% of worldwide infections, we identified a hitherto unrecognized adaptation to the antigen-processing machinery through substitutions at subtype-specific motifs. Multiple HLA variants presenting epitopes situated next to a given subtype-specific motif drive selection at this subtype-specific position, and epitope abundances correlate inversely with the HLA frequency distribution in affected populations. This adaptation reflects the sum of intrapatient adaptations, is predictable, facilitates viral subtype diversification, and increases global HIV diversity. Because low epitope abundance is associated with infrequent and weak Tcell responses, this most likely results inboth population-level immune evasion and inadequate responses in most people vaccinated with natural HIV-1 sequence constructs. Our results suggest that artificial sequence modifications at subtype-specific positions invitro could refocus and reverse the poor immunogenicity of HIV proteins. © 2014 The Authors.